2014
DOI: 10.1016/s1995-7645(14)60101-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the growth and development of mosquito larvae of Culex quinquefasciatus (Diptera: Culicidae) treated with extract from leaves of Pseudocalymma alliaceum (Bignonaceae)

Abstract: The study demonstrated for the first time, the larvicidal activity of the essential oil and hydrolat of Pseudocalymma alliaceum; aqueous, ethanol and methanol extracts inhibited the normal growth and development of mosquito larvae, prolonging and delaying larval and pupal duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…), and C. quinquefasciatus treated with leaf extracts of Pseudocalymma alliaceum (Granados‐Echegoyen et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…), and C. quinquefasciatus treated with leaf extracts of Pseudocalymma alliaceum (Granados‐Echegoyen et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…We found that the treatment of chloroform and ethyl acetate extracts of S. argel resulted in the prolongation of Cx. pipiens larval Dua et al 2009, Tom et al 2009, Granados-Echegoyen et al 2014. Few studies have reported on the effects of larvicidal plant extracts against nontarget organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Taxonomic identification was made by the curator of the Herbarium CIIDIR-OAX, and a sample for future reference was deposited in the research laboratory. The leaves were washed with tap water, placed on newspaper to dry indoors, and pulverized to powder by a mechanical mill (Granados-Echegoyen et al 2014).…”
Section: Methodsmentioning
confidence: 99%